Analisis Problematika Guru Dalam Mengintegrasikan Islam Pada Pembelajaran Biologi Di Madrasah Aliya Payakumbuh Dan Lima Puluh Kota - Salli Al Fadila; Ardi Ardi (LP2M UIN Ambon, 2025)
The integration of Islamic values in biology learning in madrasahs is important to develop scientific understanding while also shaping students’ religious character. However, its implementation still faces various challenges. This study aims to analyze the problems experienced by teachers in integrating Islamic values into biology learning at Madrasah Aliyah in Payakumbuh City and Lima Puluh Kota Regency. This research used a descriptive approach with a survey method. The research subjects were biology teachers at Madrasah Aliyah in the area. Data were collected through questionnaires and interviews and then analyzed descriptively. The results showed that the main obstacles include teachers’ lack of understanding of the concept of integrating Islam and biology, teachers’ educational background which is predominantly in the field of science, limited integrated learning resources, and the lack of training related to integrative learning. These conditions cause the integration of Islamic values in biology learning to not yet be implemented systematically. Therefore, efforts are needed to improve teachers’ competencies through training, the provision of integrated teaching materials, and support from madrasah policies.